2019
DOI: 10.1088/1361-6595/ab2c64
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent kinetic analysis of trapped electrons in a magnetically expanding plasma

Abstract: A deep understanding of the kinetic properties of the electrons in a magnetic nozzle (MN), which is attracting attention as an acceleration stage for thrusters, is of great significance as it directly contributes to the development of the MN performance. In the sense that a conversion of the electron momentum to the ion kinetic energy determines the characteristics of the MN, fundamental research on the kinetic feature of a magnetically expanding plasma has focused on the spatial distribution of the electron p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…The adiabatic caseᾱ = 0 corresponds toγ = 5/3 and, as the relative heat flux increases,γ decreases. For instance, the intermediate value α = 7/2, extracted from figure 10(c), o yieldsγ ≈ 1.2, a value close to some experimental evidence [26][27][28][29]39]. Implementing the crude closure (37) in the energy equation (33) yields the known law between the electric potential fall and the polytropic coefficient, [34] e|φ…”
Section: Iv2 Electron Heat Fluxessupporting
confidence: 70%
“…The adiabatic caseᾱ = 0 corresponds toγ = 5/3 and, as the relative heat flux increases,γ decreases. For instance, the intermediate value α = 7/2, extracted from figure 10(c), o yieldsγ ≈ 1.2, a value close to some experimental evidence [26][27][28][29]39]. Implementing the crude closure (37) in the energy equation (33) yields the known law between the electric potential fall and the polytropic coefficient, [34] e|φ…”
Section: Iv2 Electron Heat Fluxessupporting
confidence: 70%
“…The 2D magnetic field topology may influence the formation of the doubly-trapped regions, and therefore have a direct impact in the local electron cooling. As commented before, Kim et al [24,25] also found different polytropic indices when varying the strength and configuration of the magnetic nozzle.…”
Section: Iv3 Differences Between the Pm And So Thrustersmentioning
confidence: 64%
“…Little and Choueiri in [23] characterized the axial variation of macroscopic quantities in a RF plasma beam and investigated the electron cooling phenomena, comparing its results with a fluid 1D model that included electron heat conduction and revealing the critical need for improved 1D models to describe the MN expansion. More recently, experimental studies performed by Kim et al in [24,25] showed the coexistence of adiabatic expanding electrons and isothermal confined electrons along the MN of an ECR thruster. In this sense, the requirement for accurate experimental data and validation of advanced theoretical models for MNs is clear.…”
Section: Introductionmentioning
confidence: 99%
“…those flowing downstream with the ions) tend to be adiabatic (i.e. γ=5/3 in three dimensions), while confined ones (included double-trapped) are isothermal [401], [402]. Further evidences are needed.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…Many of these measurements to be carried out in the laboratory require high-quality, sophisticated, diagnostics equipment, such as accurate thrust balances, magnetic probes, and non-intrusive and intrusive devices able to characterize the non-Maxwellian VDFs of the ions and (mainly) the electrons. For instance, although there is some experimental evidence of the presence of doubly trapped electrons [401], [402], a good characterization of them under different conditions is primordial due to their probable large influence in the plasma expansion profiles. Also, measuring the beam temperature anisotropy has been proven to be very challenging and seems to require designing specific probes.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%